Closed system of couplings in generalized thermo-elastoplasticity - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the field equations of the generalized coupled thermoplasticity theory are derived using the postulates of classical thermodynamics of irreversible processses.
Keywords: thermodynamic potentials; couplings effects; stresses; deformations; temperature; entropy; enthalpy; constitutive and rate equations; yield surface; plastic potential